SISTEM INFORMASI MANAJEMEN WARUNG INTERNET (WARNET) BERBASIS GOOGLE MAPS API (STUDI KASUS : KABUPATEN KARANGANYAR) - Abdul Aziz; Khilliyatul Lubbi (IJAI (Indonesian Journal of Applied Informatics), 2016)
Department of Communication and Information Karanganyar (Dishubkominfo) as one of the agencies that help the government affairs have many tasks, one of which is to manage the licensing of establishment cafe. In managing the cafe licensing establishments ranging from the filing of the cafe establishment licensing recommendations to come out of issue on establishment licenses, Dishubkominfo still use manual way, so that all the data the cafe were stored in Microsoft Excel, Microsoft Word, or even print out. Management of the job as it causes inefficiencies and difficulties at the time of filing.Given these problems, then built a system to manage permissions establishments cafe in Karanganyar equipped cafe spread map location using the Google Maps API. With this system, applicants only need to be brought to Dishubkominfo file when the file has been ascertained completely and correctly by the Dishubkominfo through the system. In addition, the system can facilitate the task of starting from the submission of recommendations by the applicant until the exit cafe issue recommendation permits the establishment of Dishubkominfo.The system created tested using two methods, the methods and use tools blackbox GT Metrix. By using blackbox, the system has a success rate (functional received) with a range of 98%, and not suskes about 2%. While testing using GT Metrix shows the average performance of the Page Speed Score of about 40% and about 78% YSlow performance.